Author Correction: Mitochondria-specific drug release and reactive oxygen species burst induced by polyprodrug nanoreactors can enhance chemotherapy - Wenjia Zhang (Nature Portfolio, 2019)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.